2014
DOI: 10.1017/prp.2014.8
|View full text |Cite
|
Sign up to set email alerts
|

Information System Innovation as a Social Action: The Case of Career and Vocational Helping Systems

Abstract: I n the past 10 years, under the common problems of unemployment of people with a higher education and the devaluation of diplomas, the concepts and practices of higher education governance have emerged and have gradually been embedded in university operations. Higher education in Taiwan faces the same problems as the rest of the world. Thus, guided by policies of the Taiwanese Ministry of Education (TMOE) and fuelled by the media, the education-job gap is becoming a discursive truth. With this background, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…S.H. Liu et al, 2015;Wang, Shiahhou, Ben Wu, & Liu, 2014 -reported the process and outcomes of the design and implementation of vocational systems designed to enhance career and study choices for university students. Only one paper out of 19 in JPRP used qualitative methods and emphasised critical reflection (Su, Pan, & Chen, 2014 As a consequence of these observations, and considering the positivist and quantitative empirical focus of research training in the Asian region, we are not confident that participatory action research (Dick, 2015) is going to make headway as a rallying point for applied social psychological research in Asia.…”
Section: Content Of the Themed Issues: Quantitative Empiricismmentioning
confidence: 99%
See 1 more Smart Citation
“…S.H. Liu et al, 2015;Wang, Shiahhou, Ben Wu, & Liu, 2014 -reported the process and outcomes of the design and implementation of vocational systems designed to enhance career and study choices for university students. Only one paper out of 19 in JPRP used qualitative methods and emphasised critical reflection (Su, Pan, & Chen, 2014 As a consequence of these observations, and considering the positivist and quantitative empirical focus of research training in the Asian region, we are not confident that participatory action research (Dick, 2015) is going to make headway as a rallying point for applied social psychological research in Asia.…”
Section: Content Of the Themed Issues: Quantitative Empiricismmentioning
confidence: 99%
“…S.H. Liu et al, 2015;Wang, Shiahhou, Ben Wu, & Liu, 2014 -reported the process and outcomes of the design and implementation of vocational systems designed to enhance career and study choices for university students. Only one paper out of 19 in JPRP used qualitative methods and emphasised critical reflection (Su, Pan, & Chen, 2014).…”
Section: Content Of the Themed Issues: Quantitative Empiricismmentioning
confidence: 99%
“…They both view career choice as a meaningful process requiring give and take between the disciplinary technology, academic curriculum, and student, who is to be treated as lifelong learner to be cultivated, rather than a worker to be conveniently steered. Wang et al (2014) offer an alternative IS that functions like a navigation system, based on the principle of adaptive development that allows students to explore the fit between his or her interests and possible majors and professions, as well as the functions of different types of learning encountered across different curricula. Finally, their IS offers a school-to-work transition module that 'helps students define their scope of employment possibilities with their overall learning' , linking their course work and interest with jobs available in the market.…”
Section: Introduction To the Articles In The Thematic Special Issuementioning
confidence: 99%
“…With these concerns came calls for a more socially engaged Asian social psychology (Atsumi, 2007) and proposals for a more action research orientation in social psychology research in the region (Liu, Ng, Gastardo-Conaco, & Wong, 2008). But, social psychology research of this type is still not well represented in the published literature, with articles from the previous thematic Special Issue (Su, Pan, & Chen, 2014; Wang, Shiahhou, Wu, & Liu, 2014) being some of the few exemplars. More time and advocacy might be needed before more progress in this movement for action research oriented social psychology is seen, and the thematic Special Issue series hopes to be a forum within which this movement can take more concrete forms.…”
mentioning
confidence: 99%